Consensus Guidelines for the Use of Fluorescence Imaging in Hepatobiliary Surgery. Issue 1 (July 2021) - Wang, Xiaoying; Teh, Catherine S. C.; Ishizawa, Takeaki; Aoki, Takeshi; Cavallucci, David; Lee, Ser-Yee; Panganiban, Katherine M.; Perini, Marcos V.; Shah, Sudeep R.; Wang, Hongguang; Xu, Yinzhe; Suh, Kyung-Suk; et al.
Abstract : Objective: To establish consensus recommendations for the use of fluorescence imaging with indocyanine green (ICG) in hepatobiliary surgery. Background: ICG fluorescence imaging has gained popularity in hepatobiliary surgery in recent years. However, there is varied evidence on the use, dosage, and timing of administration of ICG in clinical practice. To standardize the use of this imaging modality in hepatobiliary surgery, a panel of pioneering experts from the Asia-Pacific region sought to establish a set of consensus recommendations by consolidating the available evidence and clinical experiences. Methods: A total of 13 surgeons experienced in hepatobiliary surgery and/or minimally invasive surgery formed an expert consensus panel in Shanghai, China in October 2018. By the modified Delphi method, they presented the relevant evidence, discussed clinical experiences, and derived consensus statements on the use of ICG in hepatobiliary surgery. Each statement was discussed and modified until a unanimous consensus was achieved. Results: A total of 7 recommendations for the clinical applications of ICG in hepatobiliary surgery were formulated. Conclusions: The Shanghai consensus recommendations offer practical tips and techniques to augment the safety and technical feasibility of ICG fluorescence-guided hepatobiliary surgery, including laparoscopic cholecystectomy, liver segmentectomy, and liver transplantation. Abstract : Supplemental Digital Content is available in the text